REKONSTRUKSI PENAFSIRAN WANPRESTASI DALAM PERJANJIAN FIDUSIA TERHADAP EKSEKUSI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Piki Hendiko Siregar; Muhamad Abas; Yuniar Rahmatiar; Ana Ximenes Sousa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
In financing practices in Indonesia, fiduciary guarantees play a crucial role for both creditors and debtors. However, their implementation often creates inequality because the determination of default is made unilaterally by the creditor. Constitutional Court Decision No. 18/PUU-XVII/2019 presents a new interpretation that emphasizes justice, legal protection for debtors, and the importance of the judicial process. The purpose of this study is to understand the impact of this shift in the interpretation of default on the validity and implementation of fiduciary guarantees in financing practices in Indonesia, as well as to analyze the legal considerations of Constitutional Court Decision No. 18/PUU-XVII/2019 regarding the validity of execution and legal protection for creditors and debtors. This study uses a normative juridical methodology with a statutory and conceptual approach. Data were collected through a literature review of legal norms, Constitutional Court decisions, scientific doctrines, legal writings, and supplemented with secondary data from the Financial Services Authority (OJK) and the Indonesian Financing Companies Association (APPI). The results of the study indicate more specifically that after the issuance of Constitutional Court Decision No. Based on Decision No. 18/PUU-XVII/2019, there was a 35% decrease in reports of disputes over the execution of fiduciary guarantees in district courts during the 2020–2023 period, reflecting increased compliance by financing institutions with the principle of due process of law. Determination of default can no longer be made unilaterally by creditors, but must be done through a fair and proportional legal mechanism. This decision strengthens legal protection for debtors, affirms the principle of due process of law, and requires system adjustments by financing institutions, thus making an important contribution to civil law reform, particularly in the implementation of fairer, more equal, and constitutional fiduciary guarantees in Indonesia.